Zonal flow energy ratio evolution during L-H and H-L transitions in EAST plasmas - 赵海林 兰涛 刘阿娣 孔德峰 沈华刚 吴捷 刘万东 俞昌旋 张炜 徐国盛 万宝年 (Plasma science & technology, 2017)
The essential role of zonal flow in the L-H transition and the suppression of turbulence have been studied with a long range correlation technique using Langmuir probe arrays in EAST tokamak.Two toroidally localized probe arrays are used to measure the zonal flow during L-H transition and H-L back transition.The energy ratio of the low frequency zonal flow to the total drift wave turbulence is calculated.During ELM-free H mode,the energy ratio is higher than that in L mode,which reveals the important role of zonal flows in regulating turbulence amplitude in L-H transition.